Industrial Training Report: Pahang Public Library Corporation / Muhammad Azri Samsudin - Samsudin, Muhammad Azri (Faculty of Information Management, 2020)
The Industrial Training subject (JMC690) is a subject that needed to be taken by final year students. Industrial training refers to work experience done during the program of study that is relevant to professional development prior to graduation. The duration for internship around 5 months. This training was conducted at Pahang Public Library Corporation in Kuantan. Pahang. During the industrial training. the trainee is needed to contribute to the activities o/ the 111orkplace and to meet the same demands of 11·ork production and responsibility expected by the organization o/ its regular employees. All the tasks and duties given to the trainee purposely to prepare. develop and gain new knowledge, skills and visualize the real environment of work. Tasks also been given lo the trainee ·which are daily routine where trainee were required to record it in logbook and special project which required trainee to create and implement in order to pass the subject.